Laying Eggs of Pomacea canaliculata L. on Oryza sativa L. in Various Ways of Plant Cultivation in Village Tulus Ayu, Sub District Belitang - Arsi Arsi; Eka Putri Jarda; Suparman SHK; Harman Hamidson; Khodijah Khodijah; Yulia Pujiastuti; Bambang Gunawan; Rahmat Pratama; Abu Umayah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Rice is a widely cultivated crop in Indonesia that the crop becomes a food crop with many pests and diseases. As happen in Belitang, the area many rice cultivation infested by golden snails because Belitang is a center of rice production with the biggest irrigation structure in the region. The golden snails prefer to live in submerged areas. Furthermore, the snail produces a high number of eggs in one ovulation which may produce a high number of golden snails and cause serious damage on rice to mage harvest failure. The  research of this know the number of eggs packets of golden snails laid in two rice cultivations with different ages and varieties. The method applied in the study was a survey method for which samples were taken purposively, by following certain intervals in every row of rice plants.  The observation was made to calculate the number of snail egg packets. The result showed that in the two different rice cultivation there were different numbers of snail egg packets. The difference might be caused by different environmental factors between both locations where a lower water surface caused a higher number of snail eggs.